Psychological aspects of sport-related concussions - Bloom, Gordon A.; Caron, Jeffrey G. (Routledge research in sport and exercise science, 2019)
Recognition of concussion as a serious injury, informed by neurological and physiological research, is now commonplace in sport. However, research on the psychology of concussive injury--its psychological implications and outcomes, and psychological interventions for prevention and recovery--has largelybeen overlooked. This is the first book to explicitly and authoritatively set out the psychological aspects of sport-related concussion from a multidisciplinary and global perspective The book attempts to offer a global understanding of the injury by presenting an historical overview; exploring the psychological implications of sport-related concussion and the influence of gender and sociocultural context on concussive injury and recovery; setting out practical guidance on working with special populations suffering from concussive injuries; and discussing the theoretical and methodological considerations for research on concussion and future directions for this research. Written by a group of leading international experts and offering a hitherto underdeveloped perspective on this crucial area of sports injury research, this book is crucial reading for any upper-level student, researcher, sport scientist, coach, or allied health professional working on sport-related concussion. It is also valuable reading for students and researchers interested in the psychosocial processes that impact injury and recovery or general professional practice in sport psychology